RANCANG BANGUN ALAT MONITORING DAYA DAN PEMUTUS ALIRAN LISTRIK BAGI PELANGGAN PLN BERBASIS IoT - Sagita Rochman; Afif Nuril Musthofa; Muchammad Rizky Firmansyah (Universitas PGRI Adi Buana Surabaya, 2024)
Along with the modern Indonesian society's need for electricity consumption, the level of electricity consumption continues to increase. Electricity consumption among postpaid PLN customers with single-phase connections is often poorly regulated due to inadequate monitoring of power usage and frequent payment delays between the 1st and 20th of each month. This study involved the development of a monitoring device designed to track power usage for single-phase PLN customers. Additionally, an electricity circuit breaker was created that can be controlled remotely via the officer's smartphone. This monitoring system uses PZEM-0004T as the sensor. The voltage, current, power and energy data will be read by the sensor and then sent by the ESP8266 to the Internet of Things (IoT) based Blynk Website. This breaker tool uses a relay as an electrical circuit breaker on the customer side. With this tool, it is possible to reduce illegal use of PLN electricity and reduce the number of arrears in customer electricity bill payments to PLN.